Protective effects of Colla Corii Asini Collagen Peptides on D-galactose injection combined with UVB irradiation-induced aging in mice. - Qingdi Luo; Song Zhang; Zhuo Sun; Zhihao Wang; Qiulin Yue; Xin Sun; Li Tian; Baojun Li; Kunlun Li; Chen Zhao; Lin Zhao; Le Su (PLoS ONE)
Skin aging, autonomic mobility, memory function and physical deterioration are important features of aging, and effective anti-aging treatments are important in slowing down these processes. The objective of this research was to evaluate the protective effect of Colla Corii Asini (Ejiao) Collagen Peptides (CCACPs) on D-galactose (D-gal) injection combined with UV irradiation-induced senescence in mice. BY-HEALTH collagen oral solution (Bcos) was used as a positive control. Behavioural experiments showed that CCACPs significantly improved voluntary activity, learning memory and exercise endurance in aging mice. Elisa results showed that CCACPs reduced the levels of matrix metalloproteinase-1 (MMP-1) and MMP-3 in the skin, acetylcholinesterase (AChE) in the brain, and alanine aminotransferase (ALT) and azelaic aminotransferase (AST) in the liver of mice, while increasing the levels of collagen I in the skin and SOD in the brain. RT-qPCR revealed that CCACPs reduced the expression of p16, p19 and p21 genes in the liver and hippocampus, as well as the expression of IL-6 in the skin. Histological analysis of brain hippocampus, liver and skin confirmed the protective effects of CCACPs. The findings indicated that CCACPs may potentially slow the aging effects caused by D-galactose and UVB exposure in mice by reducing cellular senescence and oxidative stress levels. The results of this research provide the scientific basis for continuing to advance the extraction of collagen peptides from Colla Corii Asini as a potential anti-aging therapy.